Ectogenesis and The Tyranny of Reproduction (International Journal of Innovative Research in Engineering & Management, 2021)
To the extent that (complete) ectogenesis liberates woman from  her reproductive role, this article imagines liberation. Even  without human babies, ectogenesis undermines the biological  paradigm that underpins existing gender classifications and labor  divides. I began by presenting a feminine oppression theory based  on 1960s radical feminists who see oppression as biological.  Restrictive social meanings are loaded onto biology as well as the  body as cultural products in this approach. Then, I suggest that  exogenesis be used to replace two types of assisted gestation, both  of which are seen as invaginations of restrictive attitudes about  women's roles. Gender specific, pronatalist, as well as geneticist  norms include surrogacy and uterine transplant. These actions  stem from preconceived notions about women's value.  Developing technologies, such as exogenesis, that undercut the  presumed link between biology and gender is beneficial to (trans inclusionary radical) feminist ideals. Exogenesis raises questions  about who qualifies in this gender identification and how we  respect those who identify as women. As a consequence,  ectogenesis may enable a more radical reimagining of the parents  and community than has previously been possible.
Keywords: Ectogenesis; Gender; Pronatalist; Reproduction; Surrogacy